2021
DOI: 10.1111/bcpt.13661
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin A promotes the transdifferentiation of primary keloid myofibroblasts into adipocyte‐like cells

Abstract: Keloid is a type of unusually raised scar. Botulinum toxin A (BTX-A) has a great application potential in keloids treatment. Here, we investigated the functional role of BTX-A in keloids. We separated keloid tissues and normal skin tissues from keloid patients and found that the expression of myofibroblast markers, α-SMA, Collagen I, and Collagen III was increased in the keloid tissues as compared with normal skin tissues. Keloid fibroblasts derived from keloid tissues were treated with TGF-β1 to induce the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Botulinum toxin type-A (Botox), well known for its muscle paralyzing activity for cosmetic concerns, appears to have an inhibitory effect on fibroblasts and collagen remodeling activity [ 11 , 12 ]. Its emerging off-label uses as intradermally injected micro-dosed Botox for aesthetic concerns, e.g., improving skin texture is an interesting area of research [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin type-A (Botox), well known for its muscle paralyzing activity for cosmetic concerns, appears to have an inhibitory effect on fibroblasts and collagen remodeling activity [ 11 , 12 ]. Its emerging off-label uses as intradermally injected micro-dosed Botox for aesthetic concerns, e.g., improving skin texture is an interesting area of research [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of elastin in keloids was described by Russel et al 14 a long time ago in cultures of keloid fibroblasts. Hellstrom et al 15 reported a week distribution of collagen III in keloids, while more recently, Hsu et al 16 and Dai et al 17 described Very few data are available about keloid sublocations. The microarray analysis published by Seifert et al 13 about three keloids from various localization (chest, abdomen and upper back) showed a higher collagen I expression in the periphery than in the centre.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the SP-NK1R pathway, other possible mechanisms of action of BTX-A in inhibiting hypertrophic scars need to be explored. Multiple pathways such as TGFβ/Smad, TGF-β/MMPs and BMP4/Smad were reported to be mediated by BTX-A in the regulation of collagen (41)(42)(43). Furthermore, BTX-A has also been proved to reduce the secretion of pro-inflammatory factors by targeting SNAP23, SNAP25 and TLR2/MyD88 signaling (44,45).…”
Section: Discussionmentioning
confidence: 99%